Evaluation of a dedicated outpatient hip fracture clinic. (27th November 2021) - Ratnayake, Hasanka; Crabtree, Amelia; Hunter, Peter; Parikh, Seema; Tay, Brenton; Anthonisz, Brian; Moran, Chris
Abstract: Objectives: There is a lack of guidance on how to manage the multiple post‐discharge issues of older people following minimal trauma hip fracture. We developed a geriatrician‐staffed outpatient service for people aged ≥65 years admitted with a hip fracture who were not discharged to a nursing home. We aimed to evaluate the potential benefits of the addition of a dedicated hip fracture follow‐up clinic by measuring the actions performed by such a clinic. Methods: We evaluated the potential benefit of the clinic through a retrospective review of the medical records of all those referred to the clinic over a 2‐year period. Results: A total of 80 people were provided a clinic appointment, with 43 (54%) attending. The median age of clinic attendees was 81 years. A total of 40/43 (93%) of attendees received inpatient rehabilitation in a sub‐acute facility before discharge. At the dedicated outpatient clinic, multiple issues were identified and managed including further fall reduction strategies ( n  = 12), commencement of anti‐resorptive medications ( n  = 11) and medication deprescribing ( n  = 11). Conclusions: We found that the introduction of a dedicated hip fracture outpatient clinic identified and managed a broad range of issues. It is unclear if these needs would have been met by previously existing services. Further work is required to clarify whether managing these issues translates into improved patient outcomes and whether a dedicated clinic is a cost‐effective practice of achieving this.